Effect of Anticoagulant Administration on the Mortality of Hospitalized Patients With COVID-19: An Updated Systematic Review and Meta-Analysis - Jiang, Luojia; Li, Yupei; Du, Heyue; Qin, Zheng; Su, Baihai (Frontiers in Medicine, 2021)
Background: Anticoagulation is generally used in hospitalized patients with COVID-19 as thromboprophylaxis. However, results from different studies comparing the effect of anticoagulation on the mortality of COVID-19 patients with non-anticoagulation are inconclusive. Methods: Our systematic review included observational trials if they studied anticoagulant therapy in hospitalized patients with COVID-19 for mortality or bleeding events. Dichotomous variables from individual studies were pooled by relative risks (RR) and their 95% confidence interval (95% CI) using the random-effect model. Grading of Recommendation Assessment, Development and Evaluation was used to assess the quality of evidence. Results: A total of 11 observational studies enrolling 20748 hospitalized COVID-19 patients overall were included. Compared with non-anticoagulation therapy, a pooled meta-analysis of these studies showed that anticoagulation therapy was associated with lower mortality risk (RR 0.70, 95%CI 0.52¬-0.93, P=0.01). The evidence of benefit was stronger among critically ill COVID-19 patients in the intensive care units (RR 0.59, 95%CI 0.43-0.83, P=0.002). Additionally, severe bleeding events were not associated with the administration of anticoagulants (RR 0.93, 95% CI 0.71-1.23, P=0.63). Conclusion: Among patients admitted to hospital with COVID-19, the administration of anticoagulants was associated with a decreased mortality without increasing the incidence of bleeding events.